Avaliação das atividades antifúngica, antioxidante e citotóxica dos monoterpenos (r)-(+)-citronelal, (s)-(-)-citronelal, 7-hidroxicitronelal - Oliveira, Heloisa Mara batista Fernandes de (2016)
Serious infections caused by opportunistic fungal pathogens such as Candida genus, have been increasingly common in immunocompromised patients. The spread of drug-resistant fungi is one of the most serious threats to the successful treatment of fungal diseases, in addition, some drugs are very toxic, hindering adherence to therapy. In this context, the monoterpenes have stood out for having various pharmacological activities such as fungicide and bactericide. It also stands out the antioxidant activity of these compounds by being able to react and inactivate the different reactive species produced during a cellular oxidative stress. Based on this, the antifungal, cytotoxic and antioxidant effect of the monoterpenes (R)-(+)-citronellal (RC), (S)-(-)-citronellal (SC) and 7-hydroxycitronellal (7-OH) were studied. For the analysis of the antimicrobial potential of monoterpenes was used with the in silico analysis software Pass online. For the realization of antifungal studies used the microdilution test with different fungal strains of Candida for evaluation of minimum inhibitory concentration (MIC). In addition, it was determined the Minimum Fungicidal Concentration (MFC) for seeding on plates. In carrying out cytotoxicity studies and antioxidant was used human red blood cells obtained from the transfusion unit of the University Hospital Lauro Wanderley/UFPB. For the antioxidant studies used the techniques with phenylhydrazine and hydrogen peroxide. The study showed that the in silico monoterpenes RC, SC and 7-OH were more likely to be active in percentage, compared to fungal microorganisms. The antifungal activity of experiments revealed that the RC and SC monoterpenes promoted strong antifungal effect with MIC50 of 256 μg/mL for strains of Candida albicans and Candida tropicalis and fungicidal action for presenting CFM50 512 μg/mL. The monoterpene 7-OH showed strong antifungal effect for both strains of Candida albicans and for Candida tropicalis strains with MIC50 of 256 μg/mL and MIC50 512 μg/mL, respectively, and fungicidal action with CFM50 512 μg/mL and 1024 μg/mL. The monoterpenes RC, SC and 7-OH showed no oxidant opposite effect to human erythrocytes. Furthermore, the front monoterpenes had antioxidant effect against phenylhydrazine and hydrogen peroxide. RC analysis of cytotoxicity, SC and 7-OH front of haemolysis erythrocytes showed values below 25% for all blood types tested at a concentration of 256 μg/mL. Given these results, it was possible to infer that the stereoisomerism of RC and SC monoterpenes did not interfere in the tested activities. In conclusion, these results suggest that the RC, SC-OH and 7 show antifungal and antioxidant effect with low cytotoxic effect.